Evaluation of nutrition and performance parameters in Division 1 collegiate athletes - Shoemaker, M. E.; Dicks, N. D.; Northrup, M. J.; Daughters, S. W.; Krings, T. N.; Barry, A. M. (Nutrients, 2024)
Background: Testing and evaluating athletes is necessary and should include performance, body composition, and nutrition. The purpose of this study was to report assessments of dietary intake, VO2max, and body composition in D1 collegiate athletes and examine relationships between these assessments. Methods: Dietary intake was assessed with 3-day recalls and compared to recommendations, and body composition was assessed via bioelectrical impedance analysis (BIA) (n = 48). VO2max was evaluated using a graded exercise test (GXT) with a verification bout (n = 35). Reliability between "true" VO2max and verification was determined. Correlations and regressions were performed. Results: Energy, carbohydrate, and micronutrient intake was lower than recommendations. Mean VO2max was 47.3 and 47.4 mL·kg-1·min-1 for GXT and verification, respectively. While correlations were apparent among dietary intake, VO2max, and body composition, percent fat-free mass (%FFM) predicted 36% of VO2max. Conclusions: Collegiate athletes are not meeting energy and carbohydrate recommendations and exceed fat recommendations. Vitamin D and magnesium were low in all sports, and iron and calcium were low in females. VO2max ranged from 35.6 to 63.0 mL·kg-1·min-1, with females below average and males meeting typical values for their designated sport. Assessing D1 athletes can provide guidance for sports dietitians, coaches, and strength and conditioning specialists to track and monitor nutrition in athletes.